Решите уравнение 1.(х+12)^2=х(х+8)2.(х-3)(х+1)=(х-2)^2

Решите уравнение  1.(х+12)^2=х(х+8) 2.(х-3)(х+1)=(х-2)^2
Гость
Ответ(ы) на вопрос:
Гость
1уравнение x^2+24x+144=x^2+8x x^2+24x-x^2-8x=-144 16x=-144 x=-9  2уравнение x^2+x-3x-3=x^2-4x+4 x^2-2x-x^2+4x=4+3 x=7
Гость
[latex]1)(x+12)^{2} =x(x+8) \\ x^{2} +144+24x= x^{2} +8x \\ x^{2} +24x- x^{2} -8x=-144 \\ 16x=-144 \\ x=-144:16 \\ x=-9 \\ \\ \\ (-9+12)^{2} =3^{2} =9 \\ -9*(-9+8)=-9*(-1)=9[/latex] [latex]2)(x-3)(x+1)=(x-2)^{2} \\ x^{2} +x-3x-3= x^{2} +4-4x \\ x^{2} -2x-3- x^{2} -4+4x=0 \\ 2x=7 \\ x=3.5 \\ \\ (3.5-3)(3.5+1)=0.5*4.5=2.25\\(3.5-2) ^{2} =1.5^{2} =2.25[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы